Germination ecology of five arable Ranunculaceae species. (22nd May 2015) - Torra, J; Royo‐Esnal, A; Recasens, J; Westerman, Paula
Summary Germination and emergence are critical life stages for annual plants and so their full understanding is essential for managing arable plant populations. This study investigated the most important species‐specific environmental cues that regulate seed germination and emergence (temperature and light) of the arable Ranunculaceae species Consolida orientalis, Consolida pubescens, Delphinium gracile, Delphinium halteratum ssp. verdunense and Nigella gallica, to propose management strategies for their preservation in agro‐ecosystems. Growth chamber and outdoor pot experiments were conducted for two consecutive seasons to analyse light (complete darkness or 12 h light) and temperature (5/10, 5/15 and 10/20°C) requirements and emergence patterns. The relative light germination requirement (ΔGlight), which extends from −100 (complete darkness) to 100 (light), was estimated. Weibull functions were fitted to observed emergence (%) in pots. For all species, germination was higher in complete darkness than with a light regime (−60 < ΔGlight < −95). This dark requirement indicates better germination for buried seeds. A tillage operation just after seed shed is therefore recommended. Consolida spp. germinate and emerge almost exclusively in autumn–winter, while Delphinium spp. and N. gallica can also germinate in spring. These arable plants would be able to adapt to delayed sowings, an important strategy for avoiding early‐emerging competitive weeds. Facultative winter‐germinating species could face early herbicide treatments if sufficient emergence occurs in winter–spring. These results bring new information to help develop conservation strategies for these species in agro‐ecosystems.